Patient‐Reported Fatigue Associated with Joint Histopathology in Rheumatoid Arthritis - Diyu Pearce‐Fisher; Melanie H. Smith; Bella Y. Mehta; Edoardo Spolaore; Edward DiCarlo; Dongmei Sun; Susan M. Goodman (ACR Open Rheumatology)
Objective Fatigue is important for patients with rheumatoid arthritis (RA) but is poorly understood. We sought to study associations of fatigue with clinical features, disease activity, and synovial histology. Methods Patients meeting the American College of Rheumatology/EULAR 1987 and/or 2010 RA criteria were recruited before elective total joint replacement. Demographics, RA characteristics, tender and swollen joints, erythrocyte sedimentation rate (ESR) and C‐reactive protein, and patient‐reported fatigue, categorized as mild, moderate, or severe, were collected. Hematoxylin and eosin stains of sectioned synovium were systematically scored by a pathologist. Relationships between fatigue and studied variables were evaluated with Kendall's tau. A directed acyclic graph (DAG) was used to illustrate associations of exposures, outcome variables, mediators, and confounders. Multivariable ordered logistic regression was used to further study associations. Results Of 160 included patients, 85.6% were women, with a median age of 63.5 (55.25–71.40) and mean disease activity scores in 28 joints using ESR (DAS28‐ESR) of 3.91 (SD 1.3). There were no differences in comorbidities across fatigue categories. Fatigue correlated with DAS28‐ESR, synovial lining hyperplasia (SLH), anxiety, depression, and pain. In the DAG, DAS28‐ESR was associated with fatigue, full mediation by pain, partial mediation by depression and anxiety, and confounding by female sex. SLH was independently associated with fatigue but did not confound the relationship between DAS28‐ESR and fatigue. SLH was affected by synovial lymphocytic inflammation. In multivariable models, female sex, DAS28‐ESR, and SLH were all associated with higher fatigue. Conclusion Although fatigue is associated with DAS28‐ESR, it is also associated with SLH independently of disease activity.